A Development and Feasibility Study of a Peer Support Telephone Program in Rheumatoid Arthritis. Issue 6 (September 2018) - Shadick, Nancy A.; Zibit, Melanie J.; Iannaccone, Christine K.; Thrower, Rebecca; Sowell, Nancy F.; Weinblatt, Michael E.; Solomon, Daniel Hal; Cui, Jing
Abstract : Supplemental digital content is available in the text.